Efektivitas Sosialisasi Outbreak Response Immunization (ORI) Terhadap Pelajar di Desa Laweyan Kecamatan Sumberasih Kabupaten Probolinggo - Vernanda, Elisa Pingky; Afianti, Julia; Gustafiani, Diana Claudya; Tukiman, Tukiman (Jurnal Administrasi Pemerintahan Desa, 2024)
Diphtheria is a highly contagious disease, and is caused by the gram-positive bacteria Corynebacterium diphtheriae toxin strain. This disease is characterized by inflammation at the site of infection, especially the mucous membranes of the pharynx, larynx, tonsils, nose and also the skin. The number of diphtheria cases in East Java as of March 2023 is 51 cases spread across 26 districts/cities with a total of 4 deaths. DPT immunization in Indonesia began in 1976 and was given 3 times, namely to babies aged 2, 3 and 4 months. Furthermore, DPT immunization was included in the School Children's Immunization Month (BIAS) program in 1984 with the aim of further increasing protection against diphtheria. The method used is socialization. Socialization was carried out through the delivery of material related to the meaning of diphtheria, symptoms of contracting diphtheria, solutions for preventing diphtheria, as well as breaking the chain of diphtheria spread through Outbreak Response Immunization (ORI). The service carried out in the form of socialization aims to increase knowledge and break the chain of diphtheria spread. The research method used in the success of this service activity is descriptive qualitative using four theories of effectiveness, namely: target accuracy, program socialization, achievement of program objectives, and program monitoring. This activity shows an increase in the knowledge of elementary school students in Laweyan regarding knowledge and prevention of diphtheria disease.